Is Islamic Banking’s Role in Third-Party Funds Becoming Significant? : Evidence from CASA and Time Deposits in Indonesia (2020–2024) - Novi Lailatul Fitri; Rovila El Maghviroh; Indra Suwandi (Perisai : Islamic Banking and Finance Journal, 2026)
This study investigates the dynamics of third-party fund (TPF) mobilization within Indonesia’s dual-banking system, focusing on the comparative roles of Islamic banks (SB) and conventional banks (CB) from 2020 to 2024. By decomposing TPF into two components—CASA (demand and savings deposits) and time deposits (TD)—the research offers novel insights into market share shifts and inter-system interdependencies. Using a quantitative approach, the analysis draws on 60 months of official banking data from the OJK and employs descriptive statistics, time-series trend analysis, non-parametric and comparative tests, cross-correlation, and ARIMA modeling to capture structural dynamics and substitution effects. Findings indicate that CB maintains dominance with an average TPF market share exceeding 90%, despite a statistically significant downward trend. Conversely, SB records steady but moderate gains, primarily within CASA, while TD remain largely stagnant. SB exhibits greater volatility in growth rates, signaling heightened sensitivity to market shocks. Cross-correlation results reveal strong substitution effects between CB and SB in CASA products, whereas SB’s TD demonstrate weaker interdependence with CB counterparts. ARIMA modeling further confirms CB’s market share as highly predictable and structurally stable, contrasting with SB’s more volatile and less forecastable pattern. This study contributes by introducing a structural comparison of CASA and TD between SB and CB—a rarely adopted approach in previous literature, which typically treats TPF as a homogeneous variable. The results suggest that SB’s relative market share gains reflect CB’s slower expansion rather than accelerated SB growth.